DIABETIC FETOPATHY - PATHOGENESIS, PROGNOSIS, PERINATAL AND NEONATAL OUTCOMES - Ольга Ивановна Мищенко; Павел Михайлович Крюков; Кира Борисовна Мозес; Вадим Гельевич Мозес; Светлана Ивановна Елгина; Елена Владимировна Рудаева; Наталья Степановна Черных (The Publishing House Medicine and Enlightenment, 2020)
The aim of the research - to carry out an analytical review of modern sources of scientific literature, covering pathogenesis, prognosis, perinatal and neonatal outcomes in diabetic fetopathy. Materials and methods. The analysis of 50 domestic and foreign sources of literature on this topic. Results. Based on the results of the analysis of scientific data, the understanding of the etiology and pathogenesis of diabetic fetopathy has been updated. The review describes possible clinical manifestations, perinatal and neonatal complications associated with diabetic fetopathy. Conclusion. Diabetic fetopathy is associated with a risk of perinatal and neonatal complications, which makes it an urgent problem. The analysis shows that this pathology requires further study.